(untitled) (Journal of Tourism & Development, 2024)
Nowadays, more and more people are concerned about their well-being and their mental and emotional health, and travelling is one of the ways to satisfy these needs (Bhalla et al., 2021). In this context, a series of new concepts related to types of tourism have appeared in recent years, which have led several authors to show their interest in these new areas, such as spiritual tourism (Collins-Kreiner, 2020). Spiritual tourism is a topic that has been discussed in various scientific studies, especially since 2017. The spiritual tourist seeks to harmonize the physical (external) journey with an inner journey, so that it is possible for tourists to explore their "self" (Halim et al., 2021). The main objective of this study was to understand the potential of the Terceira Island to develop a non-religious spiritual tourism product, according to the perceptions of the Azorean supply agents. Through the results, it can be concluded that the agents interviewed recognize that there is strong potential to the development of the spiritual tourism product but acknowledge that spiritual tourism is not yet well established on the island, despite being a Portuguese region with many success factors for this growth.